2019
DOI: 10.1016/j.socnet.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Do terrorists make a difference in criminal networks? An empirical analysis on illicit drug and narco-terror networks in their prioritization between security and efficiency

Abstract: By using Social Network Analysis (SNA), this study empirically analyzes five PKK Affiliated narco-terror and five illicit drug networks in the Turkish context to identify and compare their approach to the security-efficiency tradeoff. Results revealed that although terrorist members are in key roles and powerful positions (central and intermediary), average scores of cohesion and centrality of narco-terror networks seem to be only slightly more security driven than those of illicit drug networks. However, anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
(124 reference statements)
0
7
0
Order By: Relevance
“…Broadly speaking, studies on drug crime networks shed light on the composition of networks involved in drug dealing or trafficking, both in terms of structural organization and individual roles within groups. Some studies focused on resilience and disruption and used SNA to assess how drug-related criminal networks, such as drug trafficking organizations or online drug markets, evolved over time, reacted to change, or identified points of disruption [e.g., 27 , 61 , 63 , 73 , 81 , 86 , 90 , 118 ]. For example, Ünal [ 90 ] compared the structure of illicit drug trafficking networks against narco-terror networks using network measures to assess whether they prioritized a dense and efficient structure with visible central players or a more secure structure with short paths of information flow and small subgroups of trusted connections.…”
Section: Resultsmentioning
confidence: 99%
“…Broadly speaking, studies on drug crime networks shed light on the composition of networks involved in drug dealing or trafficking, both in terms of structural organization and individual roles within groups. Some studies focused on resilience and disruption and used SNA to assess how drug-related criminal networks, such as drug trafficking organizations or online drug markets, evolved over time, reacted to change, or identified points of disruption [e.g., 27 , 61 , 63 , 73 , 81 , 86 , 90 , 118 ]. For example, Ünal [ 90 ] compared the structure of illicit drug trafficking networks against narco-terror networks using network measures to assess whether they prioritized a dense and efficient structure with visible central players or a more secure structure with short paths of information flow and small subgroups of trusted connections.…”
Section: Resultsmentioning
confidence: 99%
“…The members would tend to limit their communications to those they share more affiliation with, even though communication across the entire network better harnesses its complete resources (Baker & Faulkner, 1993; Ouellet et al, 2017). The competing prediction, the Goal × Risk hypothesis, suggested that networks respond to risks depending on the goals (Morselli et al, 2007; Ünal, 2019). High versus low communication risks limits members' communication to affiliates only when an ideological goal is under pursuit.…”
Section: Discussionmentioning
confidence: 99%
“…Other findings suggest that goal-type influences how networks respond to risk (Morselli et al, 2007;Ünal, 2019). When an organization seeks to attain material benefits, they tend to strive for efficiency, seemingly ignoring the risks potentially due to perceived time pressure (Morselli, 2009;Morselli et al, 2007).…”
Section: The Goal × Risk Hypothesismentioning
confidence: 99%
“…Bright and Delaney, 2013). While there is evidence for systematic differences in the structural features of different kinds of criminal network (Bichler et al, 2017); there is also evidence that the differences between networks such as drug trafficking, terrorism and legitimate economic activity are not as large as previously thought (Ünal, 2019;Wood, 2017). Further, different kinds of criminal networks, different criminal activities and different illicit exchanges are frequently interconnected (Asal et al, 2015;Bright et al, 2015;Calderoni, 2012;; as well as being embedded within broader social settings (Dwyer and Moore, 2010;van de Bunt et al, 2014).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%